Serum total bile acid levels assist in the prediction of acute intussusception with abdominal type Henoch-Schonlein purpura in children - Yu, Sijie; Feng, Wei; Wang, Yi; Zhao, Maoyuan; Tu, Yuying; Guo, Zhenhua (Frontiers in Pediatrics, 2023)
Background: The severe acute abdomen associated with Henoch-Schonlein purpura (HSP) is an acute intussusception (AI). There is no reliable specific marker for AI with abdominal-type HSP. The serum total bile acid (TBA) level is a new prognostic marker associated with the severity of intestinal inflammation. The purpose of this study was to identify the prognostic value of serum TBA levels for the diagnosis of AI in children with abdominal-type HSP. Methods: A retrospective study of 708 patients with abdominal-type HSP was conducted, with demographic data, clinical symptoms, hepatic function index, immune function markers, and clinical outcomes assessed. Patients were divided into two groups: HSP (613 patients) and HSP with AI (613 patients) (95 patients). The data were analysed using SPSS 22.0. Results: Of the 708 patients, the serum TBA levels were higher in the HSP with AI group than in the HSP group (P < 0.05). Logistic regression analysis showed that vomiting (OR = 396.492, 95% CI = 14.93-10529.67, P<0.001), haematochezia (OR =87.436, 95% CI = 5.944-1286.214, P = 0.001), TBA (OR = 16.287, 95% CI = 4.83-54.922, P< 0.001), and D-dimer (OR = 5.987, 95% CI = 1.892-15.834, P = 0.003) were independent risk factors for abdominal-type HSP with AI. Receiver operating characteristic (ROC) curve analysis showed that the optimal cut-off serum TBA value (sensitivity = 91.58%, specificity = 84.67%, AUC=93.6524%) was >3 μmol/L for predicting AI in children with abdominal-type HSP. In this group of HSP patients with AI, a serum TBA level ≥ 6.98 μmol/L was significantly associated with an increased incidence of operative treatment (51.85% vs. 75.61%, P = 0.0181), intestinal necrosis (9.26% vs. 29.27%, P = 0.0117), and length of hospital stay (15.76±5.31 vs. 10.98±2.83 [days], P<0.0001). Conclusion: In children with HSP and AI, the serum TBA level was significantly higher. A novel but promising haematological indicator, the serum TBA level, helps identify HSP with and without AI and predicts intestinal necrosis in HSP with AI.